2023
DOI: 10.3390/ijms24076613
|View full text |Cite
|
Sign up to set email alerts
|

Malic Enzyme 1 (ME1) Promotes Adiposity and Hepatic Steatosis and Induces Circulating Insulin and Leptin in Obese Female Mice

Abstract: Malic Enzyme 1 (ME1) supports lipogenesis, cholesterol synthesis, and cellular redox potential by catalyzing the decarboxylation of L-malate to pyruvate, and the concomitant reduction of NADP to NADPH. We examined the contribution of ME1 to the development of obesity by provision of an obesogenic diet to C57BL/6 wild type (WT) and MOD-1 (lack ME1 protein) female mice. Adiposity, serum hormone levels, and adipose, mammary gland, liver, and small intestine gene expression patterns were compared between experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Several studies have shown that ME1 may be involved in adiposity and hepatic steatosis. For example, a study in rats with ME1 deficiency found that ME1 may promote adiposity and hepatic steatosis and induce circulating insulin and leptin, supporting the therapeutic targeting of ME1 for obesity, diabetes, and hepatic steatosis ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that ME1 may be involved in adiposity and hepatic steatosis. For example, a study in rats with ME1 deficiency found that ME1 may promote adiposity and hepatic steatosis and induce circulating insulin and leptin, supporting the therapeutic targeting of ME1 for obesity, diabetes, and hepatic steatosis ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 97%
“…This cofactor has a significant impact on the synthesis of fatty acids. ME1 actively participates in lipogenesis and maintains the delicate equilibrium between glucose and fatty acid metabolism (37). In a recent investigation by Leng et al in 2019, the researchers aimed to examine the influence of dietary fat supplementation on the expression of ME1 in the liver of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of NADPH required for biosynthesis accounts for more than 80% of the total intracellular NADPH, while most of the NADHP used for biosynthesis is used to synthesize fatty acids . NADPH produced through the series of catalytic reactions of ME1 is mainly used in biosynthesis, such as lipogenesis and cholesterol synthesis . Previous studies have found that most of the NADPH required for adipogenesis in 3T3-L1 cells is provided by ME1 .…”
Section: Discussionmentioning
confidence: 99%
“…41 NADPH produced through the series of catalytic reactions of ME1 is mainly used in biosynthesis, such as lipogenesis and cholesterol synthesis. 42 Previous studies have found that most of the NADPH required for adipogenesis in 3T3-L1 cells is provided by ME1. 31 Considering the role of ME1 in adipogenesis, its expression may be regulated at multiple levels.…”
Section: Research On the Regulation Mechanism Of Apa In Different Bio...mentioning
confidence: 99%